2014
DOI: 10.1177/0885066614523918
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality After Pneumonia in Cardiac Surgery Patients

Abstract: Pneumonia remains a serious complication in patients operated for cardiac surgery and is associated with increased hospital mortality and reduced long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
5
33
0
2
Order By: Relevance
“…Comparable with our results, Angus et al [20] reported a 30-day mortality of severe CAP patients of 15%, and a recent multicenter European study analyzing 1106 ICU patients with CAP demonstrated a 28-day mortality of 17% [21]. To our knowledge, data on 1-year mortality of ICU patients with pneumonia are rare [22][23][24]. None of these studies was conducted in an all-medical ICU where pneumonia was the primary reason of stay.…”
Section: Discussionsupporting
confidence: 87%
“…Comparable with our results, Angus et al [20] reported a 30-day mortality of severe CAP patients of 15%, and a recent multicenter European study analyzing 1106 ICU patients with CAP demonstrated a 28-day mortality of 17% [21]. To our knowledge, data on 1-year mortality of ICU patients with pneumonia are rare [22][23][24]. None of these studies was conducted in an all-medical ICU where pneumonia was the primary reason of stay.…”
Section: Discussionsupporting
confidence: 87%
“…Although a significant amount of research has focused on prevention 5‐8 and the cost of treating 9 ventilator‐associated pneumonia following cardiac surgery, the recent analysis of over 5000 prospectively enrolled cardiac surgery patients by Ailawadi et al 1 highlights the important point that nearly one‐third of postoperative pneumonias may be diagnosed after discharge from the index admission. While the development of postoperative pneumonia has been associated with significant in‐hospital mortality ranging from 23.7% 10 to 28%, 11 Ibanez et al 11 also demonstrated a significant association with reduced five‐year survival. Overall, Ailawadi et al 1 estimated that the development of postoperative pneumonia after cardiac surgery is associated with a nearly ninefold increased risk of mortality at postoperative day 65 and a nearly 2‐week increase in index length of stay 1 …”
Section: Introductionmentioning
confidence: 99%
“…Ventilator-acquired pneumonia (VAP) is a common postoperative complication and accounts for a large part of post-cardiac surgery morbidity and mortality. Incidence of VAP depends on numerous factors, including pulmonary collapse and atelectasis during cardiopulmonary bypass (CPB), lowering of bronchial arterial blood flow and systemic inflammation response syndrome during and after CPB [ 1 6 ].…”
Section: Introductionmentioning
confidence: 99%